Archaeal type IV pili and their involvement in biofilm formation - Pohlschroder, Mechthild; Esquivel, Rianne N. (Frontiers in Microbiology, 2015)
Type IV pili are ancient proteinaceous structures present on the cell surface of species in nearly all bacterial and archaeal phyla. These filaments, which are required for a diverse array of important cellular processes, are assembled employing a conserved set of core components. While type IV pilins, the structural subunits of pili, share little sequence homology, their signal peptides are structurally conserved allowing for in silico prediction. Recently, in vivo studies in model archaea representing the euryarchaeal and crenarchaeal kingdoms confirmed that several of these pilins are incorporated into type IV adhesion pili. In addition to facilitating surface adhesion, these in vivo studies also showed that several predicted pilins are required for additional functions that are critical to biofilm formation. Examples include the subunits of Sulfolobus acidocaldarius Ups pili, which are induced by exposure to UV light and promote cell aggregation and conjugation, and a subset of the Haloferax volcanii adhesion pilins, which play a critical role in microcolony formation while other pilins inhibit this process. The recent discovery of novel pilin functions such as the ability of haloarchaeal adhesion pilins to regulate swimming motility may point to novel regulatory pathways conserved across prokaryotic domains. In this review, we will discuss recent advances in our understanding of the functional roles played by archaeal type IV adhesion pili and their subunits, with particular emphasis on their involvement in biofilm formation.